Evaluation of Humoral Immunity in Oral Cancer Patients from a Nigerian Referral Centre - Akinmoladun, Victor I. (Springer India, 2012)
The immune system is central in the body’s defense against non-self. Immunoglobulins and acute phase proteins have been reported to play active roles in carcinogenesis. This prospective longitudinal study was carried out to determine the state of humoral immunity in Nigerian oral cancer patients relative to controls. Twenty newly diagnosed untreated cases of oral squamous cell carcinoma recruited from our centre were included in the study. The controls included 20 apparently healthy and HIV negative volunteers. Serum immunoglobulin classes and acute phase proteins were measured using immunoplates. IgA and ceruloplasmin showed statistically significantly elevated levels in the patients compared with controls, while increases in IgM and IgG were insignificant. The raised levels suggest a role for immunoglobulin A and ceruloplasmin in the mechanisms involved in oral cancers. Findings from this study are similar to that reported elsewhere in the literature. Further work is needed to ascertain the role and usefulness of immunoglobulins and acute phase proteins in staging, disease monitoring, therapy and prognostication.